Financing of private investment in the view of Keynes-Minsky - Carvalho, André Cutrim; Carvalho, David Ferreira (Nexos Econômicos, 2019)
The primary goal of this paper is to analyze the financing of investment and its effects on the structure of liabilities and the portfolio of a company or family and the pace of financing corporate investment assets, taking as a basis for this understanding of Keynes and Minsky. This will be described a vision of the relations of financial capitalism in terms of cash flow, and analyzed how they are related to the valuation of assets and financing of positions in the portfolio and, finally, the assumptions and elements should be implemented microeconomic analysis to macroeconomic analysis by aggregation method.